Structural diversities of squarate-based complexes: photocurrent responses and thermochromic behaviours enchanced by viologens. Issue 1 (27th November 2017) - Lin, Xiao-Yan; Zhao, Li-Ming; Wang, Dao-Hua; Wang, Yu-Kang; Li, Min; Li, Hao-Hong; Chen, Zhi-Rong
Abstract : Six new squarate-based complexes with 3-D networks, 2-D layers and 0-D clusters have been prepared.5 and6 feature the first examples of incorporating squarate with viologens in one lattice, which exhibit not only photocurrent responses but also reversible thermochromisms. Abstract : By using squarates as coordination building units, six new complexes formulated as [Mg(C4 O4 )(H2 O)2 ] n (1 ), [Pr2 (C4 O4 )2 (OA)(H2 O)4 ] n (2 ), [Eu2 (C4 O4 )3 (H2 O)8 ] n (3 ) [Cd2 (C4 O4 )2 (bpdo)(H2 O)4 ] n (4 ), [Cd(C4 HO4 )2 (H2 O)4 ]·(MV)2 ·(C4 O4 )2 (5 ), and [Cd(C4 HO4 )2 (H2 O)4 ]·(EV)·(C4 HO4 )2 (6 ), where (C4 O4 ) 2− = squarate, OA = oxalic acid, MV = methyl viologen, EV = ethyl viologen, and bpdo = 4, 4′-dipyrdiyl- N, N ′-dioxide, have been synthesized under hydro/solvothermal conditions. They present structural dimensions from 3-D networks (1, 2 ), 2-D layers (3, 4 ) to 0-D clusters (5, 6 ) based on the versatile bridged modes of squarates and the introduction of second ligands. In particular, 5 and6 are the first examples incorporating squarates (electronic-rich species) with viologens (electronic-poor species) in one lattice. Consequently, they exhibit not only photocurrent responses but also reversible thermochromism, which will be beneficial for the design of multi-functional materials.